Intensity Noise Suppression Using Dual-Polarization Dual-Parallel Modulator and Balanced Detector - Chirappanath B. Albert; Chongjia Huang; Erwin Hoi Wing Chan (IEEE Photonics Journal)
A new structure for suppressing the relative intensity noise (RIN) from an optical source is presented. It is based on an integrated dual-polarization dual-parallel modulator and a balanced detector. It only requires a single fiber connected between the transmitter and the receiver whereas two fibers are required in the conventional dual-output modulator based RIN suppression structure. Experimental results demonstrate RIN suppression of >10 dB over 1–16 GHz frequency range with and without RF signal modulation.